Stereo-Preference in the degradation of the erythro and threo isomers of β-O-4-type lignin model compounds in oxidation processes. part 2: In the reaction with hydroxyl and oxyl anion radicals under hydrogen peroxide bleaching conditions. (4th March 2017) - Posoknistakul, Pattaraporn; Akiyama, Takuya; Yokoyama, Tomoya; Matsumoto, Yuji
Abstract : We examined which isomer, the erythro or threo, of non-phenolic β- O -4-type lignin model compounds is stereo-preferentially attacked by hydroxyl radical and its conjugate base, oxyl anion radical, generated by the decomposition of hydrogen peroxide in the presence of ferric ion and its precipitates under hydrogen peroxide bleaching conditions. The intrinsic stereo-preference of oxyl anion radical was slightly toward the erythro isomer, while hydroxyl radical had a further smaller stereo-preference. These stereo-preferences can be explained by our prior knowledge that oxyl anion radical preferentially attacks the side-chain of the lignin model compounds rather than the aromatic nucleus. The amount of the degraded lignin model compounds became less great with decreasing pH, but reversely and intensively greater in the pH range below 10. This phenomenon can be attributed to the change in the decomposition mechanism of hydrogen peroxide accompanying the pH variation.